2010
DOI: 10.1111/j.1745-4573.2009.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Analysis. Fatty Acid Profiles and Mineral Contents of Meats: A Comparative Study

Abstract: The aim of this study was to compare chemical parameters, fatty acid composition and mineral contents of farm animal meats which are marketed in Turkey. Different kinds of meats were purchased from the meat market including beef, lamb, broiler, turkey, ostrich and quail meat, which are mostly preferred for different reasons by consumers. However, little information exists about the composition of meats of different farm animal species. The results of proximate analysis showed that the high level of protein (24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 40 publications
4
28
1
6
Order By: Relevance
“…Laudadio et al (2014) ) in legs and breast were 1.1 and 0.5 (Baggio et al, 2002). In comparison with current results, Karakök et al (2010) presented higher contents of DM, protein, ash and lower content of fat in thigh muscles. Jankowski et al (2012) reported no significant differences in chemical composition of raw breast meat between control group and experimental groups (addition of soybean, rapeseed, linseed oil in feed mixture).…”
Section: Nutritional Compositionmentioning
confidence: 34%
See 2 more Smart Citations
“…Laudadio et al (2014) ) in legs and breast were 1.1 and 0.5 (Baggio et al, 2002). In comparison with current results, Karakök et al (2010) presented higher contents of DM, protein, ash and lower content of fat in thigh muscles. Jankowski et al (2012) reported no significant differences in chemical composition of raw breast meat between control group and experimental groups (addition of soybean, rapeseed, linseed oil in feed mixture).…”
Section: Nutritional Compositionmentioning
confidence: 34%
“…Statistically significant (P ˂ 0.05) differences were found in content of calcium, phosphorus, magnesium, sodium, iron and zinc. In study Karakök et al (2010) was found lower content of calcium than magnesium in thigh muscle compared to present experiment. There was detected incidence of manganese and more amount of iron than zinc from analysis of microelements (Karakök et al, 2010).…”
Section: Mineral Compositionmentioning
confidence: 43%
See 1 more Smart Citation
“…However, Cavalheiro et al (2010) found a slight increasing trend in ash content as ostrich meat increased in formulas. The higher ash content when compared with raw ostrich meat, that range from 1.07% (Sales and Hayes, 1996) to 2.42% (Karakök et al, 2010) is probably due to the use of salt and spices in the formulas as reported by Fisher et al (2000); Fernández-López et al (2003);and Fernández-López et al (2006).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, ostrich meat is regarded and marketed as a healthy alternative to other red meats, due to its favourable nutritional characteristics: low levels of sodium, collagen and intramuscular fat content; favourable fatty acids profile (polyunsaturated fatty acids (PUFA)/saturated fatty acids (SFA) and ω-6/ω-3 ratios); and high levels of iron, zinc, vitamin B6, B12, and E (Fisher et al, 2000;LombardiBoccia et al, 2002;Fernández-López et al, 2003;Fernández-López et al, 2006;Karakök et al, 2010;Poławska et al, 2011;Xavier Medina and Aguilar, 2014).…”
Section: Introductionmentioning
confidence: 99%